Antibacterial, antioxidant, and haemolytic potential of silver nanoparticles biosynthesized using roots extract of Cannabis sativa plant. Issue 1 (31st December 2022) - Suman, Suman; Loveleen, Lacy; Bhandari, Meena; Syed, Asad; Bahkali, Ali H.; Manchanda, Romila; Nimesh, Surendra
Abstract: In this study, Cannabis sativa roots extract has been employed for the biosynthesis of silver nanoparticles (AgNPs). The appearance of reddish-brown colour followed by absorption peak of AgNPs at 408 nm through UV-vis spectrophotometry suggested biosynthesis of AgNPs. The size of the particles ranged from 90–113 nm, confirmed using DLS and TEM along with zeta potential of −25.3 mV. The FTIR provided information regarding the phytochemical capping. The study was further elaborated for determining AgNPs antibacterial, antioxidant, and cellular toxicity using MIC, DPPH, MTT, and haemolytic assays, respectively. The AgNPs were significantly effective against Staphylococcus aureus (Gram-positive), as compared to that of Pseudomonas aeruginosa, Klebsiella pneumoniae, and Escherichia coli (Gram-negative). AgNPs also exhibited remarkable antioxidant potential wherein 58.01 ± 0.09% free radical scavenging was observed at a concentration of 100 µg/ml. AgNPs revealed lower cytotoxicity where cell viability was observed to be 52.38 ± 0.6% at a very high concentration of 500 µg/ml in HEK 293 cells. Further, very low toxicity was seen in RBCs i.e. 6.47 ± 0.04% at a high concentration of 200 µg/ml. Thus, the current study beholds anticipation that Cannabis sativa ethanolic root extract-mediated AgNPs may play a vital role in therapeutic.